Implementation of the Independent Curriculum in Learning Arabic Language at Muhammadiyah Boarding School (MBS) in Yogyakarta - Rambu Zainab Apriani (Universitas Muhammadiyah Enrekang, 2024)
The development of the digital era is increasingly advancing, making developments in the world of education also continue to advance and develop. Curriculum that continues to carry out evaluations and revisions makes students and teachers need to continue to adapt to its development. The aim of this study is to understand the implementation of independent curriculum in Arabic language learning at Muhammadiyah Boarding School Yogyakarta as well as to evaluate its effectiveness in achieving learning goals. With data collection using observations, interviews and also documentation. Data analysis is used using the miles and hubberman theory: data collection, data reduction, data presentation and data verification. The results of this research, revealed that 1) Muhammadiyah Boarding School Yogyakrta has implemented a free curriculum, 2) Implementation of curricula in the institution has some obstacles among them is the teacher’s competence is less than the maximum because teachers are required to master all the important components that must be mastered by students, 3) The solution offered by the institution is to carry out training for teachers.